2014
DOI: 10.1111/apa.12862
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac biomarkers indicate a need for sensitive cardiac imaging among long-term childhood cancer survivors exposed to anthracyclines

Abstract: Elevated plasma NT-proBNP or cTnAAbs indicated that childhood cancer survivors benefitted from being evaluated with modern imaging, despite normal function in conventional echocardiography. However, troponins did not seem to provide additional information on the late cardiotoxicity of anthracyclines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…LV dysfunction was present in 0%–37% of the study populations with one study having no patients with LV dysfunction 28. Cut-off values for NT-proBNP levels varied from 63 ng/L in males and 116 ng/L in females29 to 125 ng/L in males and females 15. Cut-off values for children were defined in the studies as age-specific and sex-specific values previously reported by Nir  et al 29 31 32 and Albers  et al 13 33.…”
Section: Resultsmentioning
confidence: 99%
“…LV dysfunction was present in 0%–37% of the study populations with one study having no patients with LV dysfunction 28. Cut-off values for NT-proBNP levels varied from 63 ng/L in males and 116 ng/L in females29 to 125 ng/L in males and females 15. Cut-off values for children were defined in the studies as age-specific and sex-specific values previously reported by Nir  et al 29 31 32 and Albers  et al 13 33.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, NT-pro-BNP, marker of high filling pressures, has a controversial role in early detection of cardiac dysfunction 2 . Several studies demonstrated the role of troponin I and NT-pro-BNP in assessing cardiac dysfunction in hematological neoplasia treated with anthracyclines 7 , however, other studies failed to show contribution of these biomarkers for early detection of cardiotoxicity 24 . In our study, troponin I increased early, while 3D LVEF maintained within normal ranges, persistent after CHOP completion treatment, and significantly higher in group who developed cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies, hence, validate the importance of using conventional troponin for surveillance post-chemotherapy as both a sensitive and reproducible marker of myocardial dysfunction, prior to development of HF. There is also increasing data emerging from survivors of childhood cancers which shows that cTnI and hs-TnI were not consistently elevated in patients who developed LV dysfunction on imaging [ 68 70 ]. Hence, these studies demonstrate that although troponin is a sensitive marker during and early after chemotherapy, it is not a sensitive marker for ongoing surveillance of subclinical cardiotoxicity post-chemotherapy, when compared to other biomarkers such as NPs.…”
Section: Cardiac Troponinmentioning
confidence: 99%